Enslaved body, greatness of soul. A critique of Thomistic anthropology from the conflict between natural slavery, magnanimity, and delayed animation - González Fernández, Enrique (Logos. Anales del Seminario de Metafísica, 2025)
This article seeks to uncover an internal conflict within Thomas Aquinas’s anthropology, stemming from his synthesis of three doctrines taken from Aristotle: the theory of natural slavery, the virtue of magnanimity, and an embryology based on delayed animation. When Aquinas asserts that the rational soul is free and capable of attaining magnanimity, that certain bodies are naturally servile, and that the rational soul is infused only once the body has been fully formed (following the vegetative and sensitive souls), he appears to embrace a split anthropology that undermines his own metaphysical principle of the substantial unity of the human being.